Strategi dan Evaluasi Penanaman Karakter Disiplin dan Karakter Kepedulian Lingkungan di SMPN 6 dan MTS N Salatiga - Mutholingah Mutiara; Fatchur Rohman (Jurnal Ilmiah Wahana Pendidikan, 2022)
The goal of this reseach is describe widely how the strategy and evaluation of the building of disciplinary values and thevalue of environmental concern in SMPN 6 Salatiga and MTsN Salatiga. And also, how the curriculum system in SMPN 6 and MTSN Salatiga is related to the cultivation of disciplinary values and environmental concern values. The method used in this study is a descriptive qualitative approach, with the aim of describing how to implement strategies and evaluationsof the building of the disciplinary values and environmental concern values in SMPN 6 Salatiga and MTSN Salatiga.The results of this study showed that SMPN 6 Salatiga has implemented a strategy of building disciplinary values and environmental care values by including it values in school curriculum, habituation, school culture, rolemodel, and also extracurriculer. SMPN 6 Salatiga has been awarded as Adiwiyata school because it has included in its school curriculum education about the environment. Meanwhile MTsN Salatiga does not awarded as Adiwiyata school because it has not included in its school curriculum education about the environment but it has been implementing the education about environment into daily habit and rolemodels.